Description of Hypertension Incidence in the Working Area of Kambowa Community Health Center, North Buton Regency - Devi Savitri Effendy; Wa Zul; Akhmad Saleh; Umar Marzuki (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Hypertension is a condition in which blood pressure in the blood vessels reaches 140/90 mmHg or higher. Unhealthy eating habits and lack of physical activity contribute significantly to the development of hypertension. This disease is one of the leading causes of death worldwide because it is usually asymptomatic but can cause sudden death. According to a 2019 WHO report, approximately 1.28 billion adults aged 30 to 79 suffer from hypertension. Globally, hypertension is estimated to affect around 22% of the world's population, with about two-thirds of sufferers coming from low- to middle-income countries. In 2015, it was estimated that one in four men and one in five women suffered from hypertension. Objective: To provide an overview of the distribution of hypertension based on available data obtained from secondary health profile data in the working area of the Kambowa Community Health Center in 2024. Methods: This study used a quantitative descriptive approach using data collected from the Kambowa Community Health Center in North Buton District in 2024. Results: Based on the analysis, the highest prevalence of hypertension was found in women, namely 10.67%, with 4% receiving health services. The highest prevalence was found in Lahumako Village, namely 31 people (42%). Conclusion: Analysis of hypertension based on gender shows that women are more vulnerable than men and are influenced by factors such as service provision and place of residence. In terms of health services, there are limitations in facilities, a lack of competent health workers, irregular recording and reporting, and a lack of coordination between programs and sectors. In addition, limited human resources, suboptimal targeting processes, and low public awareness also play a role. The distribution of hypertension based on place of residence shows that Lahumoko Village has the highest number of patients, while Bubu Barat Village has the lowest number of patients, while other villages show relatively balanced figures. Keywords: Hypertension, blood pressure, prevalence, women, health services.